Application value of central venous-arterial carbon dioxide partial pressure difference in postoperative cognitive dysfunction in patients with acute aortic dissection - Lei Wang; Zhen Hong Wang; Duan Qi Zhu; Xin Yi Xie; Xin Chen; Xiao Liang Wang (Journal of Cardiothoracic Surgery)
Abstract Objective This study aims to investigate the clinical application value of the central venous-arterial carbon dioxide partial pressure difference (Pv-aCO2) in postoperative cognitive dysfunction(POCD) in patients with acute aortic dissection. Methods A retrospective analysis was conducted on the general data of 236 patients. Blood gas samples were collected from the arterial and venous lines at various time points during the surgery, including before and after the initiation of cardiopulmonary bypass (CPB), immediately after CPB initiation, before and after deep hypothermic circulatory arrest, 30 min after rewarming, and 5 min before weaning from CPB. The partial PV-aCO2 was calculated. Based on the average PV-aCO2 value, patients were divided into an observation group (PV-aCO2 > 6 mmHg, n = 112) and a control group (PV-aCO2 < 6 mmHg, n = 124). The perioperative data and Mini-Mental State Examination (MMSE) scores were compared between the two groups to assess the incidence and severity of POCD. Additionally, the expression levels of peripheral serum S100β in the two groups were compared 6 h postoperatively. Results The incidence of POCD was higher in the observation group compared to the control group, while MMSE scores and serum S100β levels were lower in the observation group. Additionally, the observation group patients with POCD had lower MMSE scores and serum S100β levels compared to the control group patients. In addition, logistic regression analysis revealed that advanced age, serum S100β levels, female gender, CPB time, unilateral brain perfusion time, hyperlipidemia, diabetes, and smoking history were all independent risk factors for postoperative POCD (all P < 0.05). Conclusion Pv-aCO2 can effectively reflect the intraoperative cerebral metabolic level in patients with acute aortic dissection and can serve as an intraoperative warning indicator for cognitive dysfunction. Its clinical recommendation for use is warranted.